Use of Random PCR (RAPD) technology to analyze systematic relationships in terrestrial bladderworts (Utricularia L.) - Rahman, Md Oliur (Bangladesh Journal of Botany, 2010)
Polymerase Chain Reaction (PCR) based technology RAPD was tested for its applicability and suitability for molecular systematics of terrestrial bladderworts. PCR was carried out and the resultant products were subjected to agarose gel electrophoresis. The banding patterns were compared among ten species of Utricularia. Out of 40 random oligonucleotide primers examined, 16 primers generated distinguishable bands. Cluster analysis, unweighted pair group method with arithmetic mean (UPGMA) and ordination approach Scatter diagram using Matrix plot were performed based on RAPD fingerprints. The UPGMA and ordination analysis revealed a clear portrayal of systematic relationships in bladderwort species which were concordant with previous studies based on morphology and molecular approaches, indicating the reliability of RAPD markers for estimation of genetic variation and species relationships in Utricularia. Key words: Utricularia; RAPD; PCR; Cluster analysis; Molecular taxonomy DOI: 10.3329/bjb.v39i1.5532 Bangladesh J. Bot. 39(1): 97-102, 2010 (June)